Saturday

August 30, 2014

August 30, 2014

Posted by **Anonymous** on Sunday, March 20, 2011 at 11:55am.

1. (cotA+cosecA-1)/(cotA-cosecA+1)=cosecA+cotA

2. (sinA-cosA+1)/(sinA+cosA-1)=

1/(secA-tanA)

**Related Questions**

trig - prove that :cosA-sinA+1/cosA+sinA-1=cosecA+cotA

trig - Establish the following identity: CosA/1-TanA + SinA/1-CotA = CosA-SinA

Maths - Hi, can someone give me the answer to this question: secA-tanA=1/4. Find...

Trig - Please help with this one. I've worked it out in so many ways and can't ...

maths(trigonometry) - prove that sinA-cosA+1/sinA+cosA-1=1/secA-tanA

Math - Match each ratio in the first row with an equivalent ratio from the ...

trig - Match each ratio in the first row with an equivalent ratio from the ...

further mathematics - Let P=(cosA sinA) (sinA cosA) Q=(cosB sinA) (sinB cosA) ...

trig - express the trig. ratios sinA,secA n tanA in terms of cotA.

mathematics trignometry - if sina, cosa, tana are in geometric progression then ...